Microencapsulation as a Tool for the Formulation of Functional Foods: The Phytosterols’ Case Study - Roberta Tolve; Nazarena Cela; Nicola Condelli; Maria Di Cairano; Marisa C. Caruso; Fernanda Galgano (Foods, 2020)
Hypercholesterolemia, which is an increase in total and low-density lipoprotein (LDL) serum cholesterol, is an important risk factor for the development of cardiovascular diseases. Lifestyle modifications underpin any action plan for reducing serum cholesterol. Phytosterols are natural compounds belonging to the triterpenes family. Thanks to their structural analogy with cholesterol, phytosterols have the ability to reduce serum LDL-cholesterol levels. Phytosterols are used to enrich or fortify a broad spectrum of food products. Like unsaturated fatty acids and cholesterol, phytosterols are easily oxidized. Microencapsulation could be a useful tool to overcome this and other drawbacks linked to the use of phytosterols in food fortification. In this review, in addition to explaining the phytosterols’ mechanisms of action, a focus on the use of free and encapsulated phytosterols for the formulation of functional foods, taking also into account both technological and legislative issues, is given.